MINERALOGICAL AND GEOCHEMICAL EVIDENCE FOR MULTI-STAGE FORMATION OF THE CHERTOVO KORYTO DEPOSIT - Tarasova Yu.I.; Sotskaya O.T.; Skuzovatov S.Yu.; Vanin V.A.; Kulikova Z.I.; Budyak E.A. (My University, 2016)
The Lena gold province is one of the largest known gold resources in the world. The history of its exploration is long, but the genesis of gold mineralization hosted in black shales in the Bodaibo synclinorium still remains unclear. The studies face the challenge of discovering sources for the useful component and mechanisms of its redistribution and concentration. This study aims to clarify the time sequence of the ore mineralization in the Chertovo Koryto deposit on the basis of detailed mineralogical and geochemical characteristics of the ore, wallrock metasomatites and the Early Proterozoic host black shales, and to assess the applicability of the Sukhoi Log model for clarifying the Chertovo Koryto origin. Geological setting. The Lena gold province is located in the junction area of the Siberian platform and the Baikal mountain region (Fig. 1). The main element of its geological structure is the Chuya-Tonoda-Nechera anticline. Its axial segment is marked by horsts composed of the Early Proterozoic rocks with abundant granitoid massifs. The Chertovo Koryto deposit is located within the Kevakta ore complex at the Tonoda uplift, the largest tectonically disturbed block between the Kevakta and Amandrak granitoids massifs. The 150 m thick and 1.5 km long ore zone of the Chertovo Koryto deposit is confined to the hanging wall of the fold-fault zone feathering the Amandrak deep fault (Fig. 2). In the ore zone, rocks of the Mikhailovsk Formation include carbonaceous shales of the feldspar-chlorite-sericite-quartz composition with nest-shaped ore accumulations of the pyrite-quartz composition and quartz veinlets. In our study, we distinguish five mineral associations resulting from heterochronous processes that sequentially replaced each other: - The earliest association related with the quartz-muscovite-sericite metasomatism and the removal of REE and other elements from the rocks and their partial redeposition; - Metamorphic sulphidization presented by scattered impregnations of pyrrhotite, as evidenced by small lenses of pyrrhotite, which are considerably elongated (axes up to 0.7 cm long) along the foliation planes (Figs 3, a, b); - Ore mineralization represented by a superimposed hydrothermal gold association with arsenopyrite (Fig. 3, d); - Late chalcophilic mineralization formed at the final stage of hydrothermal-metasomatic process (Figs 3, e, f); - Post-ore silification. Geochemical characteristics. The geochemical study of rocks and ores from the Chertovo Koryto deposit show that the rocks of the Mikhailovsk Formation are characterized by higher contents of rock-forming elements, such as of Al2O3, Fe2O3total, MgO, K2O, and P2O5, in comparison to the PAAS standards [Condie, 1993] and the black shale standard composition (SChS-1) [Petrov et al., 2004]. A characteristic feature of the ore zone is that the contents of practically all the oxides, except SiO2, tend to decrease (Table 1). The distribution of rare elements repeats the pattern established for major elements. The least metamorphosed rocks of the Mikhailovsk Formation have higher contents (up to three times) of Cu, Mo, Ba, W, As, Pb relative to the values in the PAAS and SChS-1 standards. In the ore zone, the contents of almost all rare elements are considerably reduced (Table 2). The contents of elements in the siderophile group (Co, Ni) are clearly correlated with the ore processes and increased more than twice in the area of metamorphic changes. Samples with gold-ore grade contents show the highest concentrations of Co and Ni. In our opinion, the Chertovo Koryto deposit was formed in five stages, the first two of which were pre-ore, with ore preparation, and probably considerably distant in time from the main ore-generating event. The staged formation of the Chertovo Koryto deposit correlates with the basic stages in the tectono-metamorphic history of the study region and is consistent with the model showing the formation of Sukhoi Log-type deposits.
МИНЕРАЛОГО-ГЕОХИМИЧЕСКИЕ СВИДЕТЕЛЬСТВА ПОЛИСТАДИЙНОСТИ ФОРМИРОВАНИЯ МЕСТОРОЖДЕНИЯ ЧЕРТОВО КОРЫТО
Keywords: GOLD; BLACK SHALES; MODEL OF METAMORPHIC-METASOMATIC FORMATION; THE BAIKAL-PATOM HIGHLAND (PLATEAU); золото; черные сланцы; модель метаморфогенно-метасоматического формирования; Чертово Корыто; Байкало-Патомское нагорье